Investigation of etoxazole metabolites in citrus, soil and earthworms by ultra-performance liquid chromatography with time-of-flight mass spectrometry. (July 2019) - Sun, Dali; Wang, Yunru; Zhang, Qinghai; Pang, Junxiao
Abstract: Etoxazole is a newly registered and widely used acaricide. However, its metabolites were not fully understood and might exhibit similar or even higher toxicity than parent compound. Therefore, in this study, the metabolites of etoxazole in citrus, soil and earthworms were firstly identified by an ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-QTOF/MS). Four potential metabolites in citrus, 11 in soil, and 8 in earthworms were determined. These metabolites were then further structural elucidated based on the fragment pathways, and accurate mass measurement. The distributions of etoxazole and its main metabolites (M1, M2, M3, M4 and M5) which were identified as the dehydrogenation, hydrolysis, oxidation products of etoxazole (M0) were also monitored in citrus, soil and earthworms at different exposure periods. The 45 days exposure experiment showed that M0 gradually decreased in citrus and soil samples by 80% and 28% of the initial amounts, respectively. In earthworm samples, M0 accumulated in the bodies of the worms during 24 days exposure and then decreased with time. The dissipation rate of etoxazole were citrus > earthworms > soil. Concentrations of M1 and M3 in soil were found continuously increased with time during the experimental period. Moreover, the persistence of M1 in earthworm samples was also observed. Great attention should be paid to these two compounds due to their potential risks to both environmental and human health. Highlights: Eleven metabolites of etoxazole were detected in citrus, soil and earthworms. Fragment pathways of etoxazole were evaluated in three matrices. Dissipation behaviors of etoxazole and its major metabolites were monitored. Dissipation rates of etoxazole were citrus > earthworms > soil.